Differentiation between traumatic tap and aneurysmal subarachnoid hemorrhage: prospective cohort study. (18th February 2015) - Perry, Jeffrey J; Alyahya, Bader; Sivilotti, Marco L A; Bullard, Michael J; Émond, Marcel; Sutherland, Jane; Worster, Andrew; Hohl, Corinne; Lee, Jacques S; Eisenhauer, Mary A; Pauls, Merril; Lesiuk, Howard; et al.
Abstract : Objectives To describe the findings in cerebrospinal fluid from patients with acute headache that could distinguish subarachnoid hemorrhage from the effects of a traumatic lumbar puncture. Design A substudy of a prospective multicenter cohort study. Setting 12 Canadian academic emergency departments, from November 2000 to December 2009. Participants Alert patients aged over 15 with an acute non-traumatic headache who underwent lumbar puncture to rule out subarachnoid hemorrhage. Main outcome measure Aneurysmal subarachnoid hemorrhage requiring intervention or resulting in death. Results Of the 1739 patients enrolled, 641 (36.9%) had abnormal results on cerebrospinal fluid analysis with >1×10 6 /L red blood cells in the final tube of cerebrospinal fluid and/or xanthochromia in one or more tubes. There were 15 (0.9%) patients with aneurysmal subarachnoid hemorrhage based on abnormal results of a lumbar puncture. The presence of fewer than 2000×10 6 /L red blood cells in addition to no xanthochromia excluded the diagnosis of aneurysmal subarachnoid hemorrhage, with a sensitivity of 100% (95% confidence interval 74.7% to 100%) and specificity of 91.2% (88.6% to 93.3%). Conclusion No xanthochromia and red blood cell count <2000×10 6 /L reasonably excludes the diagnosis of aneurysmal subarachnoid hemorrhage. Most patients with acute headache who meet this cut off will need no further investigations and aneurysmal subarachnoid hemorrhage can be excluded as a cause of their headache.